Dosage Precision in the ICU: Variability Between Males and Females - Meshram, Sucheta; Sabu, Nayana (Journal of Neonatal Surgery, 2025)
Background: Precision in drug dosing is crucial in intensive care unit (ICU) settings to achieve optimal therapeutic outcomes and minimize adverse drug reactions. Despite advancements in critical care pharmacotherapy, sex-based differences in drug pharmacokinetics (PK) and pharmacodynamics (PD) remain underappreciated. Objective: This comprehensive review aims to synthesize the evidence on sex-specific variability in drug dosing in critically ill patients and recommend strategies for individualized pharmacotherapy in the ICU. Methods: An extensive literature search was conducted using PubMed, Embase, and Scopus databases. Studies on sex differences in ICU pharmacology, PK/PD variations, and clinical outcomes were reviewed. Results: Significant gender differences exist in drug absorption, distribution, metabolism, and excretion. These variations influence the dosing of sedatives, analgesics, vasopressors, and antimicrobials. Physiological factors, hormonal influences, and genetic polymorphisms further modulate these differences. Conclusion: Integrating sex-specific factors into ICU drug dosing algorithms is essential for precision medicine. Future research should focus on clinical trials stratified by sex to refine dosing recommendations.